"A Little Costumed Girl at a Sci-Fi Convention": Boundary Work as a Main Destigmatization Strategy Among Women Fans. Issue 3 (2nd July 2016) - Yodovich, Neta
ABSTRACT: This article engages with destigmatization strategies among women fans. Contrary to a contemporary disposition among scholars that presents fandom as a legitimate and mainstream phenomenon, this article demonstrates how women fans are still stigmatized as childish, obsessive, and uncritical. In particular, I focus on Twilight and Harry Potter women fans and suggest boundary work as a main destigmatization strategy among them. Based on 15 in-depth interviews with Israeli women fans between the ages of 18 and 30, three main distinctions to establish boundaries were detected: between fans and nonfans, between "obsessive" and "normal" fans, and between fans and "appreciators." Through this analysis I work to expose an existing stigma regarding female-dominated fandoms and provide an in-depth analysis of their boundary work mechanisms through specific lenses of gender and age.